Comparative performance of mulberry (Morus indica L.) and subabul (Leucaena leucocephala Lam.) under diverse management regimes in a coconut based fodder production system - Reshma M Raj (Department of Silviculture and Agroforestry, College of Forestry, 2016)
The research project entitled “Comparative performance of mulberry (Morus indica L.) and subabul (Leucaena leucocephala Lam.) under diverse management regimes in a coconut based fodder production system” was carried out at Instructional Farm, College of Horticulture, Vellanikkara during 2015-2016. The main objective of the study was to assess the influence of plant density and pruning frequency on forage yield and nutritional qualities of mulberry and subabul intercropped in coconut gardens; and to explore the soil fertility changes associated with these intercropping systems. The treatments consisted of two fodder tree species; mulberry and subabul, under three levels of plant density (49,382 plants ha-1, 37,037 plants ha-1 and 27,777 plants ha-1) and three levels of pruning frequency (8, 12 and 16 weeks interval) in all possible combinations with split plot design replicated thrice. The results revealed that both subabul and mulberry produced comparable dry fodder yields under coconut plantation. However, significant variation was noted with regard to proximate composition. The CP content in fodder biomass was significantly higher and CF % lower in subabul than mulberry. However, mulberry had higher ash (6.70 %) and P content (0.58 %) than subabul. Leaf- stem ratio was found to be comparable in both the tree species. Comparing plant densities, highest density yielded more dry matter (12.48 Mg ha-1yr-1) than the lowest one (7.32 Mg ha-1yr-1), with higher leaf-stem ratio (1.34). Total N, CP and P content increased and CF % decreased at higher densities indicating closer spacing for production of tender nutritive fodder. Pruning interval had no significant influence on fresh fodder yield, whereas dry yield was higher for 12 and 16 week intervals. However, leaf -stem ratio was higher at 8 week interval, indicating more foliage production than stem fraction when harvested at shorter intervals. Pruning frequencies had profound influence on nutritive value of the forage. Harvesting at shortest interval of 8 weeks yielded fodder with maximum CP (18.51 %), and phosphorus content (1.1 %), and least CF content (41.91 %) compared to 12 and 16 weeks. Ash content (8.70 %) in fodder was significantly higher at the longest interval of 16 weeks. Comparing interaction effects, for both mulberry and subabul, planting at the highest density (49,382 plants ha-1) and pruning at shortest interval (8 weeks) yielded the maximum fodder (11.05 & 12.17 Mg ha-1yr-1 dry yields for mulberry and subabul respectively) with superior quality (T1 & T10). B:C ratio was also found to be higher in the above systems.Intercropping subabul and mulberry in coconut garden under different management practices produced significant changes in some soil parameters after the initial year of establishment. In comparison to the sole coconut plot, soil properties like OC, pH, EC, WHC and available N, P, K content significantly improved in the high yielding treatment combinations of T1 and T10. Comparing T1 and T10, all soil parameters excelled in T1 except available N content, which was higher in T10.Hence, in conclusion, forage yield and nutritive value of mulberry and subabul underneath coconut garden could be optimized at the cheapest levels by adopting a tree density of 49,382 plants ha-1 and pruning interval of 8 weeks. In comparison, subabul yielded more dry matter and CP, whereas mulberry was superior in ash and mineral content. Establishment and proper management of these tree fodders in coconut garden and feeding mixed fodders thus offers a cheap source of quality forage to Kerala farmers against the highly expensive concentrate feeds.